Activity recognition in surfing - a comparative study between hidden markov model and support vector machine - Hoettinger, H.; Mally, F.; Sabo, A. (Procedia Engineering, 2016)
The present project describes a comparative study between two different machine learning approaches, the Hidden Markov Model (HMM) and Support Vector Machines (SVMs), for activity recognition in surfing, aiming to distinguish surfing from other non- traditional (non-surfing) movements.